Recent advances in iontophoresis-assisted microneedle devices for transdermal biosensing and drug delivery - Gaobo Wang; Natsuho Moriyama; Soichiro Tottori; Matsuhiko Nishizawa (Materials Today Bio)
Integrating advanced manufacturing techniques and nanotechnology with cutting-edge materials has driven significant progress in global healthcare. Microneedles, recognized for their minimally invasive approach to transdermal sensing and drug delivery, achieve enhanced functionality when combined with iontophoresis. Iontophoresis-assisted microneedles have emerged as an innovative solution, enabling real-time biosensing and precise drug delivery within closed-loop systems. These integrated platforms represent a major advancement in personalized medicine, allowing dynamic therapeutic adjustments based on continuous feedback. This review highlights the latest developments in iontophoresis-assisted microneedles for transdermal biosensing, drug delivery, and closed-loop applications. It delves into the mechanisms of iontophoresis, assesses its advantages and limitations, and explores future directions for these transformative technologies.